Pyły drogowe jako potencjalne zagrożenie dla ekosystemów miejskich na przykładzie Zielonej Góry - Walczak, Barbara
The paper presents the results of tests performed on street dust. The material referred to in bibliography as street dust is formed by mineral and organic particles coming from soil, industrial emitants and road vehicles. In English bibliography this material is referred to as "street dust" or "urban dust", which can also be translated as "street impurities". Generally speaking, this material is surging along streets. The paper presents results of laboratory tests on samples of street dust collected on streets and soil coming from squares of green located in Zielona Góra. The street dust was collected twice in 56 points, the soil in 10 points of the city.
Keywords: metale ciężkie; pyły drogowe